The influence of surface material on the development of Desulfovibrio desulfuricans biofilms - Lopes, F. A. (2001)
Sulphate reducing bacteria have an important role in the sulphur cycle, and therefore in wastewater treatment systems. They are able to form biofilms on metallic surfaces, leading to fouling and corrosion problems. Additionally, hydrogen sulphide that is a product of their metabolism can cause serious health risks. In this study, sulphate reducing bacteria (SRB) biofilms were developed on stainless steel 304 and on polycarbonate in order to evaluate surface effect on biofilm formation. Results showed that the biofilm formed on stainless steel presented higher metabolic activity, confirmed by lactate and sulfate removals. Metal elements present in stainless steel may affect SRB activity. This can be the case of nickel that represents around 8% of stainless steel 304. Studies performed with suspended cultures of Desulfovibrio desulfuricans also showed that the presence of nickel in the media had a positive impact on bacterial activity.